The Influence of Transformational Leadership, Work Motivation, Work Environment, and Organizational Culture on Employee Performance at PT. Suriatama Mahkota Kencana Suzuya Mall Rantauprapat - Samosir, Syahnita; Syahputra, Rizki; Hutagaol, Anita Sri Rejeki (Postgraduate, University of Mataram, 2025)
This study aims to analyze the influence of transformational leadership, work motivation, work environment, and organizational culture on employee performance at PT. Suriatama Mahkota Kencana Suzuya Mall Rantauprapat. The research method used is quantitative with a survey approach, involving 52 respondents selected through purposive sampling techniques. Data collection was carried out using a questionnaire with a Likert scale, and data analysis was carried out by regression testing using SPSS software. The results of the study indicate that transformational leadership, work motivation, work environment, and organizational culture have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 82.5% indicates that these variables are able to explain changes in employee performance, while the remaining 17.5% is influenced by other factors not included in this research model. These findings emphasize the importance of the role of inspirational leaders, high work motivation, a supportive work environment, and a strong organizational culture in improving employee performance sustainably.